Psycho-Social Determinants of Acne in Rural Community of Lahore - Syma Arshad, Sadaf Sajid, Asma Kanwal, Mussab Ahmad, Maaz Ahmad, Hamna Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Acne is a common human skin disease, characterized by areas of skin with seborrhea (scaly red skin), comedones (blackheads and whiteheads), papules (pinheads), pustules (pimples), nodules (large papules) and possibly scarring. Acne affects mostly skin with the densest population of sebaceous follicles. These areas include the face, the upper part of the chest, and the back. Objectives: To determine the association between various psycho-social factors and acne. Design:Population based Case-Control Study. Place & Duration:Galvera Village, Lahore from May 2019 to July 2019. Subjects & Methods. A population based case-control study with 1:1 case to control ratio was conducetd. A total of 100 persons (50 cases and 50 controls) were recruited in the study. Selection was made on laid down criteria from adult population living in rural community of Lahore after taking due consent. Interviews were conducted through a pretested questionnaire by a 10 membered team of group 01, 4th year MBBS students of Rashid Latif Medical College, Lahore under direct supervision of Department of Community Medicine, Rashid Latif Medical College (RLMC). Data was collected, compiled and analyzed through SPSS version 25. Results: Overall 48% were males and 52% were female in the study. Among acne cases, mostly were males(70%), above the age of 30 years (80%) and educated (88%). In bivariate analysis, Acne was found more related with aggression (OR 2.302, 95% CI=1.021-5.190), anxiety(OR 3.857, 95% CI=1.670-8.911), constipation (OR 6.143, 95% CI=2.323-16.242), depression (OR 3.019, 95% CI=1.315-6.929), dusty environment (OR 2.528, 95% CI=1.112-5.744), stress (OR 4.644, 95% CI=1.981-10.883), high fat diet (OR 3.551, 95% CI=1.541-8.181), immediate rest after dinner (OR 3.841, 95% CI=1.610-9.161), introvert personality (OR 3.407, 95% CI=1.401-8.285), irregular timings of meal (OR 8.273, 95% CI=3.357-20.388), junk food (OR 4.896 , 95% CI=2.044-11.728), lack of personal hygiene (OR 4.472, 95% CI=1.355-14.755), lack of regular intake of fruits (OR5.310, 95% CI=1.913-14.745), lack of regular intake of vegetables (OR 4.162, 95% CI=1.744-9.935), lack of regular prayers (OR 2.455, 95% CI=1.097-5.494), lack of rest after lunch (OR 2.333, 95% CI=1.027-5.300), undue late night working (OR 6.612, 95% CI=2.762-15.831), high carbohydrate diet (OR 3.622, 95% CI=1.559-8.418), dandruff (OR 2.279, 95% CI=1.017-5.108), exposure to sunlight (OR 6.000, 95% CI=2.528-14.240), habit of skin scratching (OR 8.500, 95% CI=3.412-21.177), intake of carbonated drinks (OR 3.622, 95% CI=1.559-8.418), lack of cleansing before sleep (OR 4.125, 95% CI=1.792-9.497) and less intake of water (OR 4.644, 95% CI=1.981-10.883). However after multivariate analysis while controlling all other listed risk factors, acne was found more related with constipation (OR 4.012, 95% CI=1.067-15.084)), dusty environment (OR 2.639, 95% CI=1.035-6.732)), stress (OR 3.288, 95% CI=1.022-10.580), irregular timings of meals (OR 5.809, 95% CI=1.359-24.830), undue late night working (OR 3.584, 95% CI=1.251-10.271), exposure to sunlight (OR 5.194, 95% CI=1.677-16.092), habit of skin scratching (OR 6.334, 95% CI=2.378-16.873), lack of cleansing before sleep (OR 3.109, 95% CI=1.203-8.034) and less intake of water (OR 4.518, 95% CI=1.250-16.324) Conclusion: Acne was found significantly associated with constipation, dusty environment, stress, irregular timings of meals, undue late night working, exposure to sunlight, habit of skin scratching, lack of cleansing before sleep and less intake of water.